Edukasi Nilai-Nilai Karakter bagi Anak Usia 8–12 Tahun melalui Pendekatan Experiential Learning di Gomong Lama - Maria Grace Putri Edi; Karoluslina Karoluslina; Samsul Hadi; Basariah Basariah; Jumrawati Jumrawati; Zulva Amelia (Jurnal Dedikasi Madani, 2026)
This community service activity aimed to strengthen character values among children aged 8–12 years in Gomong Lama through an experiential learning approach. The activities were conducted using educational games, simulations, group discussions, storytelling, and reflective learning. The methods applied included socialization, character education activities, mentoring, and evaluation. The results showed that children demonstrated improvements in discipline, honesty, empathy, responsibility, and cooperation in daily interactions. The experiential learning approach encouraged children to actively participate and internalize character values through direct experience. This activity also increased community awareness regarding the importance of character education outside formal school environments. Kata Kunci: Pendidikan Karakter, Experiential Learning, Anak-Anak, Pendidikan Masyarakat